Proceedings of 40th International Conference on High Energy Physics — PoS(ICHEP2020) 2021
DOI: 10.22323/1.390.0984
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the muography background using the Muon Telescope (MuTe)

Abstract: Characterization of the muography background using MuTe Jesús Peña-Rodríguez PoS(ICHEP2020)984 Characterization of the muography background using MuTe Jesús Peña-Rodríguez

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Some other times, a straight line can be approximated by several particles that propagate on the same plane as a result of a local cascade. Some studies [24] have revealed that only 30% of the appropriate signal should be considered as such in the data recorded by a muon telescope. This leads to a different perspective for the muon tomography experiments where the response of the detector can be studied against extensive air shower products rather than against just the muon component.…”
Section: Classifymentioning
confidence: 99%
“…Some other times, a straight line can be approximated by several particles that propagate on the same plane as a result of a local cascade. Some studies [24] have revealed that only 30% of the appropriate signal should be considered as such in the data recorded by a muon telescope. This leads to a different perspective for the muon tomography experiments where the response of the detector can be studied against extensive air shower products rather than against just the muon component.…”
Section: Classifymentioning
confidence: 99%